2021
DOI: 10.3390/vaccines9121397
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Seasonal Influenza Vaccination and Cross-Promoting COVID-19 Vaccination: An Audience Segmentation Study among University Students

Abstract: In the response to the coronavirus pandemic, much attention has been invested in promoting COVID-19 vaccination. However, the impact of seasonal influenza should not be neglected, particularly during the winter influenza surge. Currently, most influenza vaccination campaigns target at healthcare workers or high-risk population groups, while COVID-19 vaccination programmes are targeting the whole population as a single homogeneous group. There is limited research on the promotion of influenza vaccination for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
4
15
0
Order By: Relevance
“…The good-and later, further improved-attitude towards vaccination seen in the present work is important since many studies concur that such attitudes improve the likelihood of requesting the influenza [54][55][56][57] and COVID-19 vaccines [43,48,58].…”
Section: Discussionsupporting
confidence: 58%
“…The good-and later, further improved-attitude towards vaccination seen in the present work is important since many studies concur that such attitudes improve the likelihood of requesting the influenza [54][55][56][57] and COVID-19 vaccines [43,48,58].…”
Section: Discussionsupporting
confidence: 58%
“…In a study [ 45 ] where participants received multiple in-app messages throughout the program period, the majority of participants responded to the vaccination messages and were activated immediately after receiving the first message. This phenomenon matches with important findings from a segmentation study conducted by Lee et al [ 66 ] that students with strong vaccine hesitancy will not respond to the same message no matter how times they are exposed to it. Direct repeats of the same message will only work for certain types of students.…”
Section: Discussionsupporting
confidence: 90%
“…Although healthcare and non-healthcare students have documented differences in the reasons behind influenza vaccine acceptance [ 13 , 65 ], interventions based on group difference within the student population were not reported. According to an advanced multivariate segmentation analysis conducted by Lee et al [ 66 ], university students should be segmented. The Lee et al [ 52 ] study identified four heterogenous groups with observed differences in receptivity of influenza information and vaccine acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations